Evaluation of long-term pulmonary functions after COVID-19 infection in children: a longitudinal observational cohort study - Muhammet F Korkmaz; Gülsüm E Şenkan; Şefika Elmas Bozdemir; Merve Korkmaz; İbrahim Koç; Behiye Oral (Journal of Infection in Developing Countries)
Introduction: We aimed to present the changes that may occur in pulmonary functions in children who experienced more severe coronavirus disease 2019 (COVID-19) during long-term follow-up.